The value of18F-FDG PET/CT in the management of malignant peripheral nerve sheath tumors - Benjapa Khiewvan (2018)
Purpose: Our objective was to determine how positron emission tomography (PET)/CT had been used in the clinical treatment of malignant peripheral nerve sheath tumor (MPNST) patients at The University of Texas MD Anderson Cancer Center. Methods: We reviewed a database of MPNST patients referred to MD Anderson Cancer Center during 1995-2011. We enrolled 47 patients who underwent PET/CT imaging. Disease stage was based on conventional imaging and PET/CT findings using National Comprehensive Cancer Network (NCCN) guidelines. Treatment strategies based on PET/CT and conventional imaging were determined by chart review. The maximum and mean standardized uptake values (SUVmax, SUVmean), metabolic tumor volume (MTV), total lesion glycolysis (TLG), change in SUVmax, change in MTV, and change in TLG were calculated from the PET/CT studies before and after treatment. Response prediction was based on imaging studies performed before and after therapy and categorized as positive or negative for residual tumor. Clinical outcome was determined from chart review. Results: PET/CT was performed for staging in 16 patients, for restaging in 29 patients, and for surveillance in 2 patients. Of the patients, 88 % were correctly staged with PET/CT, whereas 75 % were correctly staged with conventional imaging. The sensitivity to detect local recurrence and distant metastasis at restaging was 100 and 100 % for PET/CT compared to 86 and 83 % for conventional imaging, respectively. PET/CT findings resulted in treatment changes in 31 % (5/16) and 14 % (4/29) of patients at staging and restaging, respectively. Recurrence, MTV, and TLG were prognostic factors for survival, whereas SUVmaxand SUVmeanwere not predictive. For 21 patients who had imaging studies performed both before and after treatment, PET/CT was better at predicting outcome (overall survival, progression-free survival) than conventional imaging. A decreasing SUVmax≥ 30 % and decrease in TLG and MTV were significant predictors for overall and progression-free survival. Conclusion: PET/CT is valuable in MPNST management because of its high accuracy in staging and high sensitivity and accuracy in restaging as well as improvements in treatment planning. MTV from baseline staging studies is predictive of survival. Additionally, change in SUVmax, TLG, and MTV accurately predicted outcomes after treatment. © 2014 Springer-Verlag.